蕊希《只能陪你走一程》小说修辞手法分析 GAYA BAHASA DALAM NOVEL I WILL BE HERE WITH YOU KARYA RUI XI - Yuliandre Wijaya (Journal of Language, Literature and Teaching, 2022)
This research’s purposes are to explain the types of figures of speech used and what are the functions of those used by the author in the novel I Will Be Here with You. This research utilizes the qualitative descriptive method. The data resource is the novel itself entitled I Will Be Here with You. The data collection technique is documentation. The results of the study found as many as 12 types of figures of speech used, namely 比喻 (bǐyù) makes abstract things seem concrete, visualizes things more generally, 比拟 (bǐnǐ) gives a clear impression, helps readers understand the conveyed feelings, 夸张 (kuāzhāng) evokes strong resonance strong and imagination, accentuates elements and characteristics in the novel, 婉曲 (wǎnqū) makes it easier to accept what is written, 对偶 (duì'ǒu) gives a strong sense of rhythm and focused meaning, helps readers draw conclusions effectively, 排比 (páibǐ) increases language momentum and expression effect, emphasizes meanings, 层递(céngdì) deepens understanding and impression, 顶真 (dǐngzhēn) gives fluent expression, fresh writing style or unique writing form, 对比 (duìbǐ) accentuates thoughts, 反复 (fǎnfù) emphasizes main thoughts, written in order , has a strong sense of rhythm, 设问 (shewèn) captures attention and guides the readers’ mind, 反问 (fǎnwèn) evokes feelings.Keywords: Novel, Figures of Speech